Microwave ablation combined with apatinib and camrelizumab in patients with advanced hepatocellular carcinoma: A single-arm, preliminary study - Li, Xin; Zhang, Qiao; Lu, Qiaorui; Cheng, Zhigang; Liu, Fangyi; Han, Zhiyu; Yu, Xiaoling; Yu, Jie; Liang, Ping (Frontiers in Immunology, 2022)
Purpose The aim of this study was to assess the safety and efficacy of microwave ablation combined with apatinib [vascular endothelial growth factor receptor-2 (VEGFR-2) inhibitor] and camrelizumab [anti-programmed death-1 (PD-1) antibody] in patients with advanced hepatocellular carcinoma (HCC). Patients and methods Patients (age, >18 years) with histologically confirmed HCC and refractory to at least the standard first-line therapy were enrolled from 2 September 2018 to 17 January 2022. They first received ultrasound-guided subtotal microwave ablation. Then, beginning at 7–14 days after ablation, they were given apatinib (250 mg once daily) and camrelizumab (200 mg once every 2 weeks) until unacceptable toxicity or disease progression or death. The coprimary end points were progression-free survival (PFS) and overall survival (OS). Results Fourteen HCC patients with Barcelona Clinic of Liver Cancer (BCLC) B and C stages were retrospectively enrolled. At data cutoff, follow-up period ranged from 3.8 to 41.3 months (median, 17.4 months), and the median (95% confidence interval) duration of exposure (DE) was 6.4 (4.0–8.9) months. The PFS and OS were 10.8 (0–23.5) months and 19.3 (2.4–36.2) months, respectively. Three (21.4%) patients achieved a confirmed complete response (CR). Confirmed partial response (PR), stable disease (SD), and progression of disease (PD) were achieved in four (28.6%), four (28.6%), and three (21.4%) patients, respectively. The objective response rate (ORR) and disease control rate (DCR) were 50.0% (20.0%-80.0%) and 78.6% (54.0%-100%), respectively. The serious treatment-related adverse events included one (7.1%) case with reactive capillary hemangiomas (grade 4), one (7.1%) with hypertension (grade 3), two (14.3%) with elevated transaminase and bilirubin (grade 4), one (7.1%) with platelet count decrease (grade 4), one (7.1%) with hepatic failure (grade 4), and two (14.3%) with gastrointestinal bleeding (grades 3 and 4). Conclusions Microwave ablation combined with apatinib and camrelizumab treatment in advanced HCC patients demonstrated intriguing clinical activity and resulted in durable antitumor responses and significantly improved PFS and OS. The combination therapy is well tolerated, enabling further clinical studies.